Innovative Food Systems Pedagogy. Issue 2 (4th March 2022) - Jones, Sonya J.; Craig, Jason D.; Spencer, Mindi
ABSTRACT: Food systems students can benefit from a critically reflective, anti-oppressive, and culturally responsive classroom. In this paper, we share 37 students' reflections on their experiences in two such courses. Qualitative analysis was done in NVIVO to identify emergent themes. Students connected personal experiences of trauma, oppression, grief, as well as nourishment, resistance, and self – care to food systems case study themes. Students' reflections demonstrated how anti-oppressive and culturally responsive practices created inclusive and safe spaces for students to grapple with complex issues and share vulnerable personal experiences that deepened their learning.